Ontario Quits Coal. - Jones, W.D.
This paper discusses the many challenges facing the province of Ontario in Canada as it tries to comply with the carbon emissions reduction requirements of the Kyoto Protocol. In order to stay ahead of demand that is increasing at an average annual rate approaching one percent and to reverse a growing dependence on electricity imported from neighbors such as Quebec and New York, the province needs to increase local electricity generating capacity. To help achieve this goal, the Ontario Power Authority has come up with an Integrated Power System Plan, which involves relying heavily on renewable energy, propping up its deteriorating nuclear fleet, and making much more efficient use of its energy resources
Keywords: Integrated Power System Plan; Kyoto Protocol; Ontario; Ontario Power Authority; Climate change; Coal-fired electricity-generating plants; Electricity-generating capacity; Energy strategy; Long-term electric energy planning; Renewable energy